EFFECT OF REDUCED BEAM SECTION IN STAGGERED TRUSS FRAME STRUCTURE VIERENDEEL ELEMENT WITH EARTHQUAKE LOAD ANALYSIS - M. Farid Nurul Iman; Endah Wahyuni; Data Iranata (Journal of Civil Engineering, 2017)
The purpose of this study is to describe the effect of Reduced Beam Section in vierendeel panel element in STF system’s inelastic behavior based on earthquake load analysis. STF system is applied to 4, 6, and 10 storey building that served as office building. The structure’s system used Special Moment Resisting Frame (SMRF) system in longitudinal direction (W-E) and STF system in transversal direction (N-S). The analysis method that used in this study is nonlinear pushover analysis. Application of RBS in vierendeel panel element showed that by the increasing of storey number, the ductility of the structure was increased in both directions, while N-S direction has bigger ductility than W-E direction. Dissipation energy of the structure was also increased, especially in N-S direction. The first yielding process occurred in vierendeel panel element, and then followed by truss and diagonal chord around vierendeel panel element, while the critical condition showed still at life safety level.